Immune Effector Cell Associated Neurotoxicity (ICANS) in Pediatric and Young Adult Patients Following Chimeric Antigen Receptor (CAR) T-Cell Therapy: Can We Optimize Early Diagnosis? - Brown, Brandon Douglas; Tambaro, Francesco Paolo; Kohorst, Mira; Chi, Linda; Mahadeo, Kris Michael; Tewari, Priti; Petropoulos, Demetrios; Slopis, John M.; Sadighi, Zsila; Khazal, Sajad (Frontiers in Oncology, 2021)
The Cornell Assessment for Pediatric Delirium (CAPD) was first proposed by the Pediatric Acute Lung Injury and Sepsis Investigators Network-Stem Cell Transplantation and Cancer Immunotherapy Subgroup and MD Anderson CARTOX joint working committees, for detection of immune effector cell associated neurotoxicity (ICANS) in pediatric and adolescent patients receiving chimeric antigen receptor (CAR) T-cell therapy. It was subsequently adopted by the American Society for Transplantation and Cellular Therapy. The utility of CAPD as an early indicator of ICANS has not been fully characterized. We conducted a retrospective study of patients (n=15) receiving standard-of-care CAR T-cell products. Cytokine release syndrome (CRS) and ICANS occurred in 87% and 40% of patients, respectively. ICANS was associated with significantly higher peaks of serum ferritin. A change in CAPD from a prior baseline was noted in 60% of patients with ICANS, 24-72 hours prior to diagnosis of ICANS. The median change from baseline to maximum CAPD score of patients who developed ICANS versus those who did not was 13 versus 3, respectively (p=0.0004). Changes in CAPD score from baseline may be the earliest indicator of ICANS among pediatric and adolescent patients and warrant closer monitoring, with more frequent CAPD assessments.